Life After Being a Pathology Department Chair II - David N. Bailey MD; Mary F. Lipscomb MD; Fred Gorstein MD; David Wilkinson MD; Fred Sanfilippo MD, PhD (Elsevier, 2017)
The 2016 Association of Pathology Chairs annual meeting featured a discussion group of Association of Pathology Chairs senior fellows (former chairs of academic departments of pathology who have remained active in Association of Pathology Chairs) that focused on how they decided to transition from the chair, how they prepared for such transition, and what they did after the transition. At the 2017 annual meeting, the senior fellows (encompassing 481 years of chair service) discussed lessons they learned from service as chair. These lessons included preparation for the chairship, what they would have done differently as chair, critical factors for success as chair, factors associated with failures, stress reduction techniques for themselves and for their faculty and staff, mechanisms for dealing with and avoiding problems, and the satisfaction they derived from their service as chair. It is reasonable to assume that these lessons may be representative of those learned by chairs of other specialties as well as by higher-level academic administrators such as deans, vice presidents, and chief executive officers. Although the environment for serving as a department chair has been changing dramatically, many of the lessons learned by former chairs are still valuable for current chairs of any length of tenure.